WOMEN EMPOWERMENT THROUGH PARTICIPATION IN ANIMAL HUSBANDRY ACTIVITIES IN ADAMAWA STATE OF NIGERIA - Maryam Gidado Halilu, Halimat Kamal Bello, Gana Joseph Shallagwa, (EPRA International Journal of Multidisciplinary Research (IJMR), 2022)
This paper seeks to examine socio-economic benefits of participation in animal husbandry activities among women in Adamawa state of Nigeria. Women empowerment through animal husbandry activities which is the focus of this paper is a mechanism through which Northern Nigerian women are able to increase self-reliance in order to promote their well-being as it is believed agricultural development is a field that saddles its recipients with income generation. A sample of 154 women involved in the animal husbandry activities from the study area were selected from a study population of 255, through sample random from the seven local government areas of Adamawa State of Nigeria and a schedule was designed and administered among the respondents. The result revealed that respondents have opportunities through their participation in animal husbandry activities to enjoy some socio-economic benefits which include increase in their income, purchasing power and improved life. Most of the participants have no formal education which directly informed their participation in the programme. The study finds out that there is high rate of involvement of women in animal husbandry activities in the study area, hence most of the respondents emphasized positive changes in their socio-economic well-being. The paper therefore concludes that women involvement in animal husbandry activities is a mechanism for women empowerment and poverty alleviation in Northern Nigeria. It also concludes that the practice is a field that saddles on how to be employable and to be useful to themselves and the society.